Information skills instruction in Higher Education students using the 4C/ID model - García, Consuelo; Argelagós, Esther; Privado, Jesús (International Conference on Higher Education Advances (HEAd), 2024)
Information skills instruction continues to be a pending subject among university students despite the fact that they handle the Internet with ease, since the ability to define what is needed, to be strategic when deciding where to search and how, to select the information most appropriate and relevant and to use it properly is not routinely taught. The purpose of this article is to show how the 4C/ID model is applied to the design of this skill, the challenges encountered in its adaptation and the improvement in self-perceived efficacy by students. The results show that the model is successful and the students felt more prepared to face this type of tasks in the future.
Keywords: 4C/ID model; information skills instruction; online; higher education